1991
DOI: 10.1016/0735-1097(91)90936-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in elastic recoil after percutaneous transluminal coronary angioplasty: A quantitative angiographic study

Abstract: The immediate result of percutaneous transluminal coronary angioplasty is influenced by both plastic and elastic changes of the vessel wall. To evaluate the amount of elastic recoil after coronary balloon angioplasty, the minimal luminal cross-sectional area of the largest balloon used at highest inflation pressure was compared with the minimal luminal vessel cross-sectional area directly after final balloon deflation in 607 lesions (526 patients). Elastic recoil was defined as the difference between balloon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…Rensing et al reported that elastic recoil in aorto-ostial lesions reaches 50%. 9 Conventional balloon angioplasty causes insufficient dilatation and a high rate of restenosis 3 because of the significant radial strength and elastic properties of the aorta-ostial lesions. Thus, the conventional balloon has to be inflated to a higher pressure and this may cause significant vessel injury, unpredictable dissections, and distal embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Rensing et al reported that elastic recoil in aorto-ostial lesions reaches 50%. 9 Conventional balloon angioplasty causes insufficient dilatation and a high rate of restenosis 3 because of the significant radial strength and elastic properties of the aorta-ostial lesions. Thus, the conventional balloon has to be inflated to a higher pressure and this may cause significant vessel injury, unpredictable dissections, and distal embolization.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that early loss of procedural luminal gain may be apparent as early as 15 min after completion of conventional balloon angioplasty [7]. Lesions with an eccentric or small plaque area and/or with a small radius of curvature have been associated with accentuated elastic recoil after angioplasty [8]. Intravascular ultrasound data correlated early elastic recoil with absence of any plaque 'cracking' during balloon angioplasty [9,10].…”
Section: Introductionmentioning
confidence: 87%
“…1C). This results in an exaggerated wound healing response, involving a combination of processes, including elastic recoil [13], thrombus formation [14], inflammation [15], neointimal formation and arterial remodelling [5].…”
Section: Pathogenesis Of Restenosismentioning
confidence: 99%